Pengembangan Media Smart Home Tools Untuk Meningkatkan Kemampuan Motorik Halus Anak Usia 4-5 Tahun Di Tk Annur Bastari Pekanbaru - Azani, Aisyah Zesi; Nurlita , Nurlita; Tambunan, Novidawaty (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Early childhood is a golden age when all aspects of development grow rapidly, thus requiring appropriate stimulation through learning activities that align with children’s developmental characteristics. One important aspect that needs to be stimulated is fine motor skills, as these skills affect children’s independence in daily activities as well as their readiness for basic academic learning. Based on initial observations at TK Annur Bastari Pekanbaru, fine motor skills of some children aged 4–5 years were still not optimally developed. This study aims to develop the Smart Home Tools media as a learning medium that presents play activities related to household tasks to train hand–eye coordination and strengthen children’s finger muscles. The research employed the Research and Development (R&D) method with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. The research instruments consisted of material expert and media expert validation sheets, as well as a limited field trial. Data sources were obtained from expert validation by competent lecturers in their respective fields. The results of the limited trial showed that the Smart Home Tools media achieved a feasibility percentage of 89.58%, categorized as “Highly Feasible.” Therefore, it can be concluded that the Smart Home Tools media is suitable for use in improving fine motor skills of children aged 4–5 years at TK Annur Bastari Pekanbaru.